Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1440-1746.2005.03808.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of cytochrome P450 in patients with hepatitis C virus‐associated hepatocellular carcinoma

Abstract: There is no statistically significant difference in genetic mutant alleles between the two groups, except for the genotype of CYP2A6*4A homozygous. The frequency of this genotype in the HCC patients (0.144) is significantly higher than that in healthy Japanese (0.034; P < 0.05; odds ratio 3.36). The clinical significance related to HCC is unknown. Further evaluation of CYP2A6*4A (deletion type) in HCV-related HCC patients is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Among the 71 included studies, 42 were population-based case-control studies, 28 hospital-based case-control studies and one genome-wide association study, including total of 47,413 cancer cases and 58,546 controls (Table 1 ). The total investigated SNPs were six, of which 62 studies on the rs762551 [ 4 , 7 21 , 23 , 24 , 26 46 , 48 50 , 52 , 61 65 , 67 , 68 , 72 75 , 77 79 , 81 84 ]. Thirty five studies out of 62 were conducted on Caucasians (56.5 %), 17 on mixed populations (27.4 %) and 10 on Asians (16.1 %), including 33,181 cancer cases and 40,195 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 71 included studies, 42 were population-based case-control studies, 28 hospital-based case-control studies and one genome-wide association study, including total of 47,413 cancer cases and 58,546 controls (Table 1 ). The total investigated SNPs were six, of which 62 studies on the rs762551 [ 4 , 7 21 , 23 , 24 , 26 46 , 48 50 , 52 , 61 65 , 67 , 68 , 72 75 , 77 79 , 81 84 ]. Thirty five studies out of 62 were conducted on Caucasians (56.5 %), 17 on mixed populations (27.4 %) and 10 on Asians (16.1 %), including 33,181 cancer cases and 40,195 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Above all, ethnic differences may attribute to these different results, since the distributions of the CYP2C19 polymorphism were different between various ethnic populations. For instance, the frequencies of CYP2C19*3 polymorphism allele differs from less than 0.5% in Caucasian population [36], 12% in Chinese population [22], to 16% in Japanese populations [17]. However, several studies conducted among Middle East populations which shown a similar PMs genotypes prevalence as Caucasians found a significant association between CYP2C19 PMs genotype and cancer susceptibility [21,27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Kondoh et al (1999) reported that CYP3A4 mRNA is highly induced in nontumorous liver and maintained at variable levels in carcinoma tissues from hepatocarcinoma patients but barely detectable in normal liver from non hepatocarcinoma patients. Moreover, genetic alterations of CYPs have been reported in the development and/or progression of a subset of various cancers (Mochizuki et al, 2005;Shin et al, 2007). However, factors regulating CYP3A activity and expression have been remained limited.…”
Section: Discussionmentioning
confidence: 99%